Sudden unexplained death in childhood: A comparison of cases with and without a febrile seizure history. (29th June 2015) - Hesdorffer, Dale C.; Crandall, Laura A.; Friedman, Daniel; Devinsky, Orrin
Summary Objective We considered whether a subset of children with sudden unexplained death in childhood (SUDC) and a history of febrile seizures (FS) may parallel those in sudden unexpected death in epilepsy (SUDEP). The prevalence of a history of FS was examined, and factors that may distinguish SUDC cases with and without FS were described. Methods Characteristics were assessed in 123 consecutive children with SUDC reported to the SUDC program (4/1/11‐3/31/14) by their parents. Parental interview covered the decedent's medical history, circumstances of death, environmental factors, cause of death, and family medical history. Features of SUDC cases were compared by FS history. Results Overall, 31.7% of SUDC cases had a history of FS, among which 74.4% had simple FS. Compared to those without a history of FS, a history of FS was associated with a greater median age at death (p = 0.03) and death during the weekdays (p = 0.02). Terminal fever was similar in those with and without FS. The median time from FS to death was 6.0 months (interquartile range [IQR] 3.0–10.0). In all SUDC cases, prone position at death, death during sleep, and unwitnessed deaths predominated. Significance There are parallels among SUDC, sudden infant deaths, and sudden unexpected death in epilepsy (SUDEP) with regard to prone position, unwitnessed deaths mostly during sleep, and male predominance. In children with SUDC and a history of FS, terminal fever may increase the risk for an unwitnessed terminal seizure. The greater than expected prevalence of a FS history and the proportion with terminal fever or illness in this cohort suggests that some SUDC deaths may be seizure related and therefore have potential commonalities with SUDEP.